Endoscopic revision efficacy after clinically successful bilateral metal stenting for advanced malignant hilar obstruction. Issue 12 (17th June 2020) - Lee, Tae Hoon; Jang, Sung Ill; Moon, Jong Ho; Lee, Yun Nah; Yang, Jae Kook; Park, Jin‐Seok; Jeong, Seok; Lee, Don Haeng; Heo, Nam Hun; Park, Sang‐Heum; Lee, Dong Ki
Abstract: Backgrounds and Aim: Multiple insertions of self‐expandable metal stents (SEMS) for advanced malignant hilar obstruction (MHO) are now considered to be an effective palliative method for adequate drainage of liver volume. However, the efficacy of endoscopic reintervention in technically and clinically successful bilateral SEMS is limited. This study investigated the endoscopic revision efficacy in patients who underwent bilateral SEMS in MHO. Methods: Primary endoscopic revision using plastic or metal stents or an alternative percutaneous approach followed by secondary endoscopic revision was performed in patients who underwent clinically successful deployment of bilateral SEMS. The primary outcome was a technical success. Secondary outcomes were clinical success, adverse events, and patency duration after reintervention. Results: A total of 55 patients (83.3%) out of 66 enrolled patients underwent reintervention: primary endoscopic reintervention ( n  = 47) and secondary endoscopic revision following percutaneous drainage ( n  = 8). Intended technical success rates of primary and secondary endoscopic reintervention were 93.6% (44/47) and 87.5% (7/8), respectively ( P  = 0.47). Clinical success rates were 72.3% and 50%, respectively ( P  = 0.23). Stent malfunction rate after reintervention was 48.9% (23/47) and 37.5% (3/8) ( P  = 0.70) during follow up, and median cumulative stent patency duration was 119 and 55 days, respectively (log–rank P  = 0.68). Stent patent rate after reintervention was not different according to the time interval. In univariate and multivariate analysis for stent patency duration‐related factors after reintervention, there were no meaningful factors. Conclusion: Primary endoscopic reintervention for bilateral SEMS in MHO was feasible technically and clinically. However, there were no statistically meaningful factors for stent patency duration after reintervention.